The egghead gene product influences oocyte differentiation by follicle cell-germ cell interactions in Drosophila melanogaster. - Rübsam, Ralph; Hollmann, Martin; Simmerl, Elfriede; Lammermann, Ulrich; Schäfer, Mireille; Büning, Jürgen; Schäfer, Ulrich (Mechanisms of Development, 1998)
Oogenesis in Drosophila is a useful model for studying cell differentiation. We have analyzed the role of the egh gene in these processes with the aid of a newly isolated viable but female sterile allele. This mutation results in diverse variable defects in oogenesis. The most frequent defect being follicles that have either more or less than the normal number of 16 germ cells. This is caused by erroneous splitting and/or fusion of correct clusters of 16 cystocytes. The entire follicle has a rather flexible structure in this allele, most obvious by a highly variable position of the oocyte within the follicle. Moreover, a second oocyte can also develop in egh clusters. This is exclusively observed in aberrant follicles that are generated by the aforementioned splitting/fusion process. Surprisingly, even a germ cell which is distinct from the two pro-oocytes can differentiate into an oocyte under these circumstances. Hence, determination of the oocyte is definitely not fixed when germ cell clusters are enveloped by prefollicular cells, and interactions between follicle cells and germ cells must play an important role in oocyte specification. Molecular analysis proves that the oocyte-specific transcript of the egh gene is drastically reduced in this viable allele.
Keywords: Drosophila oogenesis; Follicle formation; Oocyte differentiation; egh function